A synopsis of the Endomychidae (Coleoptera: Cucujoidea) of Mexico - Arriaga-Varela, Emmanuel; Tomaszewska, K. Wioletta; Navarrete-Heredia, Jose Luis (Zootaxa, 2007)
The state of knowledge of Mexican Endomychidae is summarized. A checklist for all described species recorded from México is presented, including comments on taxonomy, biology and distribution. 56 species are recorded (including two subspecies); Stenotarsus marginalis Arrow is recorded for the first time from México. These species belong to 18 genera; Lycoperdinella Champion is recorded based on an undescribed species. 7 subfamilies are present in the Mexican fauna: Anamorphinae, Merophysiinae, Lycoperdininae, Stenotarsinae, Epipocinae, Eupsilobiinae and Pleganophorinae. Epipocus is the most diverse genus with 20 species, followed by Stenotarsus with 13. The highest diversity is known from Veracruz, where 30 (32?) species are known, followed by Chiapas with 12 (13?) species.